Paraneoplastic hyperleucocytosis in a melanoma patient after initiation of ipilimumab and nivolumab combination therapy - Gambichler, Thilo (J Immunother Cancer, 2018)
BACKGROUND: Paraneoplastic hyperleucocytosis (PH) is sporadically seen in patients with advanced solid tumors. CASE PRESENTATION: We report a female patient with disseminated melanoma metastases. Two days after the first dosage of combined immunotherapy using the cytotoxic T lymphocyte antigen-4 (CTLA-4) blocker ipilimumab and the programmed death receptor-1 (PD-1) blocker nivolumab the patient developed asymptomatic hyperleucocytosis (over 120.000 leucocytes per μl) associated with elevated granulocyte colony-stimulating factor blood levels. Hematological and infectious disorders could be ruled out. Although paraneoplastic hyperleucocytosis spontaneously resolved she died from progressive disease about 60 days after start of treatment. CONCLUSIONS: PH is extremely rare in malignant melanoma, however, most patients who developed this complication had preceding immunotherapies such as interleukin-2. The latter observation and the fact that our patient developed PH rapidly after initiation of ipilimumab and nivolumab immunotherapy indicate an immune-mediated mechanism which may trigger PH under unknown circumstances. The development of paraneoplastic hyperleucocytosis indicates a very poor prognosis.